Associação genômica ampla e principais genes de maturidade em soja - Bozi, Antonio Henrique (2021)
Soybean (Glycine max) is a sensitive species to the photoperiod and a legume of great interest worldwide. The flowering time and maturity are important factors that control the productivity of the crop and its latitudinal adaptation. Understanding the molecular mechanism that regulate the flowering time and maturity is necessary in order, to improve adaptability and productivity. Although four genes have been used in early maturity breeding programs, new genes and QTLs that determine maturity are continually being identified, suggesting that unknown loci exist and that govern such characteristics of interest. Thus, the objective of the present study was to identify new genomic regions (QTLs) and SNP markers associated with groups of relative maturity and to identify response genes to the soybean photoperiod/ floral induction in strains via genome wide association. A total of 5428 soybean strains from the GDM Seeds genetic improvement program, were evaluated in three countries (Argentina, United States and Brazil) regarding the maturity group (MG). Subsequently, the strains were genotyped using SNP molecular markers, using genotyping technology based on specific allele competition (KASP- Kompetitive Allele Specific PCR). In total 2669 polymorphic SNP marker were used to analyze the structure of populations and carry out the genome wide association studies (GWAS). The results of the GWAS analysis revealed a total of 29 significant SNPs (p<0,001) associated with the different maturity groups, which were distributed in 13 chromosomes, including chromosomes 1, 2, 3, 6, 7, 8, 9, 12, 13, 17, 18, 19 e 20. Nine SNPs were new loci and 20 SNPs were located within or 1.5Mb close to know QTLs. Four candidate genes (Glyma.03g169700, Glyma19g.13800, Glyma.06g216400 e Glyma.06g207800) were associated with groups of early maturation, being represented by significant markers until MGs 5.0. Another six genes (Glyma.06g204100, Glyma.06g057900, Glyma.12g089100, Glyma.12g103800, Glyma.12g073900 e Glyma.08g236300) were candidate, as they were associated with later maturity groups, being significant in MGs above 5.0. Candidate genes, including enzymes and transcription factors, are directly and directly related to the character being analyzed. The loci and markers associated with maturity groups, identified in this study can be used for the genetic improvement of soybean, through marker-assisted selection (MAS), providing genotypes with desirable maturation groups in a more agile and precise manner.